IQTISODIYOTNI RIVOJLANTIRISHDA TIJORAT BANKLARI TOMONIDAN AJRATILGAN INVESTITSION KREDITLARNING AHAMIYATI - Xikmatullayev Olimxon Asatulla o‘g‘li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article describes the ways and methods of increasing the efficiency of investment activities of banks in the economy of Uzbekistan, including the specific features of the formation of the investment portfolio of commercial banks, the analysis of the international and national investment situation of the Republic of Uzbekistan, and the analysis of loans allocated by commercial banks. statement is given. Also, the existing problems in the management of investment resources of commercial banks and ways to eliminate them, directions for increasing the investment activity and efficiency of commercial banks, as well as opinions on the effective organization of relations in the investment field of commercial banks are highlighted.